2006
DOI: 10.1002/sres.733
|View full text |Cite
|
Sign up to set email alerts
|

Functional modelling in engineering design: a perspectival approach featuring living systems theory

Abstract: Complex engineering systems (e.g. aeronautic vehicles and automobiles) consist of many different interfacing parts and are subject to numerous requirements and constraints regarding aspects of performance, manufacturability, economics, etc. Their design requires the collaboration between people from various disciplines-each retaining different, but necessary, perspectives of the system under design. Here, perspective is defined as a particular context that a human utilizes to create personally meaningful under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The proposal is an innovative contribution to the development of CBM in the context of the emerging paradigm of CE, digitalization of businesses and companies, and the aim of mitigating the metabolic rift from the early stages in an aggregate level as it is the business value chain. The quantification of this model could be incorporated into the holarchies establishing the relations and flows between entities with quantitative methods such as ecological relations [98,175], living system theory in the different levels of granularity for the modeling of the knowledge [176][177][178], contextualizing material, energy and information of the process and use of sustainable indicators for each of the entities [179]. Another aspect to consider is the incorporation of open innovation with fractal criteria (repeated at different scales) in Eco-Holonic Architecture, and agile and Lean principles in the business [180,181].…”
Section: Discussionmentioning
confidence: 99%
“…The proposal is an innovative contribution to the development of CBM in the context of the emerging paradigm of CE, digitalization of businesses and companies, and the aim of mitigating the metabolic rift from the early stages in an aggregate level as it is the business value chain. The quantification of this model could be incorporated into the holarchies establishing the relations and flows between entities with quantitative methods such as ecological relations [98,175], living system theory in the different levels of granularity for the modeling of the knowledge [176][177][178], contextualizing material, energy and information of the process and use of sustainable indicators for each of the entities [179]. Another aspect to consider is the incorporation of open innovation with fractal criteria (repeated at different scales) in Eco-Holonic Architecture, and agile and Lean principles in the business [180,181].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent research has extended the QFD method to account for stakeholders' multiple preferences and fuse them into one uniform group decision by means of fuzzy set theory [85]. Another example is [86], who observed that the key to developing complex systems lies in negotiating different perspectives such that a highly integrated and comprehensive result is achieved. A methodology is proposed that explicitly incorporates the multiplicity and diversity of perspectives encountered when designing these systems, which consist of many interfacing parts and different requirements regarding such concerns as performance, manufacturability, and economics.…”
Section: Collaborative Negotiation Approachesmentioning
confidence: 98%
“…Function modeling is an expression, representation, or description of a product or system using high-level abstract language depending on its functionality [56]. The systems can be described as process flow block diagrams or hierarchical tree models of functional behavior [57]. However, in the xDID model, adopted from the definition of embodiment function by Deng et al [53], the function is proposed at the level of the embodiment function (physical structure level), which is achieved by the combination of the integrated structure (often multiscale) and its structural strategies.…”
Section: Meta-level Embodiment Functionmentioning
confidence: 99%